2008
DOI: 10.1186/1472-6831-8-11
|View full text |Cite
|
Sign up to set email alerts
|

The Dutch version of the Oral Health Impact Profile (OHIP-NL): Translation, reliability and construct validity

Abstract: BackgroundThe purpose of this study was to make a cross-culturally adapted, Dutch version of the Oral Health Impact Profile (OHIP), a 49-item questionnaire measuring oral health-related quality of life, and to examine its psychometric properties.MethodsThe original English version of the OHIP was translated into the Dutch language, following the guidelines for cross-cultural adaptation of health-related quality of life measures. The resulting OHIP-NL's psychometric properties were examined in a sample of 119 p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
84
1
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 93 publications
(93 citation statements)
references
References 22 publications
6
84
1
2
Order By: Relevance
“…This study demonstrated that the OHIP is internally consistent (as shown by the Cronbach α). The Cronbach α for internal consistency in this study was slightly lower than in studies by van der Meulen or John (23,36), similar to values obtained by Slade and Spencer (10), and higher than those from Lopez (38).…”
Section: Percentage Of Respondentssupporting
confidence: 82%
See 3 more Smart Citations
“…This study demonstrated that the OHIP is internally consistent (as shown by the Cronbach α). The Cronbach α for internal consistency in this study was slightly lower than in studies by van der Meulen or John (23,36), similar to values obtained by Slade and Spencer (10), and higher than those from Lopez (38).…”
Section: Percentage Of Respondentssupporting
confidence: 82%
“…Our values were slightly higher than those reported in other studies (23,36). The adequate reliability on the OHIP-14s-ar was confirmed by the Bland-Altman plot (34), which showed that 95% of differences were within the limits of agreement.…”
Section: Percentage Of Respondentssupporting
confidence: 47%
See 2 more Smart Citations
“…Therefore, the OHIP-49 has been translated and validated in several countries [4][5][6][7][8][9][10][11]. A Chinese version of the OHIP was developed by Wong and McMillan [4] for the Hong Kong elderly.…”
Section: Introductionmentioning
confidence: 99%